Water planning framework for alfalfa fields using treated wastewater fertigation in Qatar: An energy-water-food nexus approach - Fatima-zahra Lahlou (17092951) (2020)
The state of Qatar is challenged by food insecurity due to its limited water resources. Considering its large industrial infrastructure and municipal water usage, treated wastewater with varying nutritional content can alleviate the stress on groundwater resources and enhance food production. Using an energy-water-food nexus approach, this study presents a planning framework that identifies the optimum allocation of 13 sources of treated wastewater to be used in cultivating alfalfa, achieving reductions in greywater footprint, energy for transportation, and carbon footprint. The treated wastewater sources are allocated according to their nitrogen-phosphorus-potassium contents to meet alfalfa requirements while respecting irrigation water standards. Results demonstrate that treated wastewater optimally provides the water and nutrient requirements to both farms. Greywater footprint, energy for transportation, and carbon footprint associated with the growth of 1 ton of alfalfa are found to be -917m3, 70 kWh and -34kg-Co2,eq for Er-rakhiya farm, and -1,770m3, 68 kWh and -18kg-Co2,eq for Wadi Al Araig farm. Other Information Published in: Computers & Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.compchemeng.2020.106999